2011
DOI: 10.1002/hyp.8219
|View full text |Cite
|
Sign up to set email alerts
|

Travel time controls the magnitude of nitrate discharge in groundwater bypassing the riparian zone to a stream on Virginia's coastal plain

Abstract: Abstract:Groundwater that bypasses the riparian zone by travelling along deep flow paths may deliver high concentrations of fertilizerderived NO 3 to streams, or it may be impacted by the NO 3 removal process of denitrification in streambed sediments. In a study of a small agricultural catchment on the Atlantic coastal plain of Virginia's eastern shore, we used seepage meters deployed in the streambed to measure specific discharge of groundwater and its solute concentrations for various locations and dates. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 51 publications
0
69
1
Order By: Relevance
“…These differences in catchment runoff sources during large rain events are important to take into account in water management practices, since a significant transport of phosphorus and nitrogen has been shown to be associated with storm events (Jordan et al, 2005;Kronvang and Bruhn, 1996;Stutter et al, 2008). Furthermore, the travel time (Flewelling et al, 2012) and origin (Clément et al, 2003) of discharging groundwater are decisive for the possibility of nitrate reduction.…”
Section: Temporal Dynamics and Catchment-scale Differences In Runoff mentioning
confidence: 99%
“…These differences in catchment runoff sources during large rain events are important to take into account in water management practices, since a significant transport of phosphorus and nitrogen has been shown to be associated with storm events (Jordan et al, 2005;Kronvang and Bruhn, 1996;Stutter et al, 2008). Furthermore, the travel time (Flewelling et al, 2012) and origin (Clément et al, 2003) of discharging groundwater are decisive for the possibility of nitrate reduction.…”
Section: Temporal Dynamics and Catchment-scale Differences In Runoff mentioning
confidence: 99%
“…For example, Galavotti (2004) and Gu et al (2007) found that most of the groundwater nitrate was denitrified during transport through a 30-cm thick organic-rich layer located directly beneath the sediment surface. For shallow groundwater, a number of studies have highlighted the denitrification potential and nitrate removal occurring during transport through the subsurface riparian zone (Fisher and Acreman, 2004;Flewelling et al, 2012;Hinshaw and Dahlgren, 2016). Stable isotopic ( 18 O), radioisotopic ( 3 H), and dissolved gas (e.g., dissolved chlorofluorocarbon gases) analyses to determine groundwater transit times to surface water indicate a wide range of transit times from several years to decades 55 Legacy Nutrient Dynamics at the Watershed Scale McGuire and McDonnell, 2006).…”
mentioning
confidence: 99%
“…For example, interception of shallow groundwater by subsurface tile drainage systems, or groundwater flow paths that are deeper than the root zone, often cause "riparian bypass" [10], in which groundwater bypasses riparian buffers. The most appropriate practice for the many drained areas on the Delmarva is wetland restoration, but this option is not attractive to many agricultural producers because of the amount of land needed to be taken out of production.…”
Section: Introductionmentioning
confidence: 99%